Air Pollution and Greenhouse Gases - Tan, Zhongchao (Springer, 2014)
Air emissions include air pollution emissions and greenhouse gas emissions. Effective air emission control requires multidisciplinary expertise in engineering, education, physics, chemistry, mathematics, medical science, psychology, agriculture, architecture, business management, economics, and politics. It is a difficult task for the author(s) of any single book to address all aspects of air emissions. The focus of this book is on engineering science and technology, upon which effective air emission control program must be built. It does not prescribe social, economic, and political factors that lie outside the scope of this book. This book aims at senior undergraduate and graduate students with educational backgrounds in mechanical, chemical, and/or environmental engineering. It can also be used by professionals with similar training background. It focuses on the basic concepts and engineering applications of technologies for the control of air emissions resulted from fossil fuel combustion. This book is divided into three parts. The general basic concepts introduced in Part I are necessary to the understanding of air emission engineering topics in Parts II and III. Part II presents the engineering applications of the principles introduced in Part I. Part III covers some emerging topics related to air emission engineering and they include carbon capture and storage, nanoaerosol, indoor air quality. Following a brief introduction to air emission in Chap. 1, Chaps. 2–4 present the general basic properties of gases and aerosol particles. They are necessary to understand the formation and behavior of air emissions. Chapters 5 and 6 present basic principles for the separation of unwanted gases and particulates from the contaminated air. These are the principles for the related engineering applications in Parts II and III such as syngas cleaning, carbon capture, and flue gas cleaning. Part II of the book introduces the strategies for precombustion (Chaps. 7 and 8), in-combustion (Chap. 9) and postcombustion (Chap. 10) air emission control, step by step, from a process point of view. While air dispersion model (Chap. 11) is a powerful tool for air quality assessment and impact prediction, air dispersion itself is also a measure for air emission control by dilution.
From Basic Concepts to Engineering Applications for Air Emission Control